Uma análise empírica sobre a relevância da oferta do serviço de correspondente bancário - Dias, Eduardo David Duarte (2016)
This article discusses the possible effects of correspondent banking services, whose definition, according to LOUREIRO (2011), is any institution that offers, in addition to their normal activities, services of financial institutions, on revenues of merchandise from a retailer drugs and non-drugs. In other words, assess whether the variable "Having Banking Correspondent", alone or in conjunction with other qualitative variables, is significant and impacts the sales of goods of this company, so that justifies the expenditure fixed with staff, equipment maintenance and safety arising from this service.